(untitled) (International journal of artificial intelligence, 2026)
This scientific article analyzes the theoretical and practical aspects of using innovative pedagogical technologies in preschool educational institutions. It also highlights the importance of applying interactive methods, information and communication technologies, and developmental education methods in the educational process. The article discusses the development of children’s intellectual potential, creativity, and independent thinking skills through innovative approaches.